Developing KPI System for Customer Services - Dragan, Illya; Smolníková, Markéta; Břešťan, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The aim of this thesis is to design and establish a Business Intelligence solution for a specific Business Unit within company at the level of all regions where this Business Unit provides its services. The main purpose of this system is to track and manage the progress of a strategic program, developed by managers themselves, which focuses on portfolio development, and cultural change. It will be used for internal purposes, namely at the level of headquarter management and further on in the regional companies. To implement this project and achieve its aim, it was necessary to analyze the available data, resources, and technical infrastructure, to propose and create a solution architecture, to test the solution, and further to validate it with stakeholders. These steps are fully described in the following chapters. Starting from the motivation for creating the solution, which is described in the business assignment. Following on to the description of the data assignment, where the data sources, technical infrastructure and basic requirements for the environment in which the solution should be created are defined. Continuing with the description of the implementation process, both working with data and its subsequent represent in Power BI Desktop / Services, and working with additional tools, like Power Automate and Power Apps, to complete all business and data assignments.
Vedoucí práce: Markéta Smolníková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses